2022
DOI: 10.21608/eajbsz.2022.253274
|View full text |Cite
|
Sign up to set email alerts
|

Study on Toxic Effects of Lead Acetate on Haematological Parameters of Adult Albino Rats and The Role of Mesenchymal Stem Cells and Flax Seeds Oil as Therapeutic Agents

Abstract: Background: Lead is a toxic heavy metal extensive in the environment. Lead induces oxidative stress. mesenchymal stem cells (MSCs) have multiplied great attention as an efficient tool in regenerative therapy. Flaxseed oil (FSO) natural source of antioxidant agents which reduced oxidative stress.Aims: The current study purposes to explore the effects of MSCs and FSO on the toxicity of lead acetate on haematological parameters. Material and methods: Forty rats were randomly divided into four groups and 10 rats p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…In line with the present investigation, Peng et al [28] found that lead exposure did not affect hematological parameters. In contrast other research indicated significant changes in different blood indices in response to lead toxicity including anemia, leukocytosis, thrombocytosis, and others [29,30] . These findings suggested that the effect of lead on hematologic parameters is possibly not linear.…”
Section: Discussionmentioning
confidence: 91%
“…In line with the present investigation, Peng et al [28] found that lead exposure did not affect hematological parameters. In contrast other research indicated significant changes in different blood indices in response to lead toxicity including anemia, leukocytosis, thrombocytosis, and others [29,30] . These findings suggested that the effect of lead on hematologic parameters is possibly not linear.…”
Section: Discussionmentioning
confidence: 91%
“…Flavonoid's biological activities are linked to their antioxidant activity via a variety of mechanisms, including “scavenging or quenching free radicals, chelating metal ions, and blocking enzyme systems that produce free radicals” (Gulcin, 2020 ; Nwozo et al, 2023 ). Flaxseed and fennel seeds show excellent antioxidant activity which helps to prevent lipid peroxidation and free radical damage; their extracts may be beneficial in the production of safe food additives (El‐shater et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%